2018
DOI: 10.1186/s13075-017-1505-8
|View full text |Cite
|
Sign up to set email alerts
|

Synovial IL-9 facilitates neutrophil survival, function and differentiation of Th17 cells in rheumatoid arthritis

Abstract: BackgroundRole of Th9 cells and interleukin-9 (IL-9) in human autoimmune diseases such as psoriasis and ulcerative colitis has been explored only very recently. However, their involvement in human rheumatoid arthritis (RA) is not conclusive. Pathogenesis of RA is complex and involves various T cell subsets and neutrophils. Here, we aimed at understanding the impact of IL-9 on infiltrating immune cells and their eventual role in synovial inflammation in RA.MethodsIn vitro stimulation of T cells was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 43 publications
2
45
1
Order By: Relevance
“…In numerous experimental autoimmune disease models, Th9 cells have been found as primary contributors to the inflammatory progression (25). Previously, it had been indicated that Th9 cells are increased in RA patients compared to healthy controls (11,26,27). Our results confirmed the findings of earlier studies regarding the significant increase in the frequency of circulating Th9 cells in RA patients.…”
Section: Discussionsupporting
confidence: 91%
“…In numerous experimental autoimmune disease models, Th9 cells have been found as primary contributors to the inflammatory progression (25). Previously, it had been indicated that Th9 cells are increased in RA patients compared to healthy controls (11,26,27). Our results confirmed the findings of earlier studies regarding the significant increase in the frequency of circulating Th9 cells in RA patients.…”
Section: Discussionsupporting
confidence: 91%
“…39 A recent study also demonstrated that IL-9 might facilitate the survival of neutrophils in rheumatoid arthritis. 40 Therefore, in our model it is possible that anti-IL-9 effectively reduced egg granulomatous inflammation and decreased inflammatory cell infiltration around the trapped eggs through mechanisms similar to those mentioned above.…”
Section: Discussionmentioning
confidence: 72%
“…As in human RA, multiple immune and inflammatory events and pathways are involved, including autoreactive Th1 and Th17 T cells, autoantibodies, proinflammatory cytokines, and activated, tissue‐destructive synovial cells . Moreover, synovial enrichment of Th9 cells shows a positive correlation with disease activity in RA, and synovial IL‐9 prolongs the survival of neutrophils, increases their matrix metalloproteinase 9 production, and facilitates Th17 cell differentiation .…”
Section: Discussionmentioning
confidence: 99%